Continuous renal replacement therapy (CRRT) program initiation in PICU of a resource limited setting: a retrospective analysis of challenges and outcomes - Jerin C Sekhar; Karthi Nallasamy; Muralidharan Jayashree; Manjinder Singh Randhawa; Namita Ravikumar; Sudeep K. C.; Suresh Kumar Angurana; Arun Bansal (BMC Nephrology)
Abstract Background Continuous Renal Replacement Therapy (CRRT) is emerging as an essential component of organ support in critically ill children. In low- and middle- income countries (LMIC), limited resources, lack of technical support, cost, and administrative issues are major barriers in initiating and sustaining a CRRT program. Methods A core team, comprising a consultant and two pediatric intensive care fellows, was assigned additional responsibility of initiating and sustaining a CRRT program in the PICU of a tertiary care teaching and referral hospital. We retrospectively reviewed the data from initiation in February 2019 till May 2023 to understand the indications, prescription details, challenges, and their relation to outcomes. Results During this period, 52 children with mean (SD) age of 7.6 (3.2) years and median (IQR) weight of 20 (17, 30) kg underwent CRRT in 71 sessions. The mean PRISM-III score was 18 (5.2), with 98.1% having multiorgan dysfunction at CRRT initiation. Acute kidney injury (53.8%), hyperammonemia (21.2%), and a combination of both (17.3%) were common indications. Continuous venovenous hemodiafiltration was the most used modality (61.5%). Median CRRT duration was 36 (20.3, 58) hours. Filter usage averaged 1.4 per patient with a median life of 35 (17, 48) hours, improving from 24 to 36 h over time. Filter clotting (33.8%), access flow issues (7%), and hemodynamic instability (4.2%) were complications encountered. Survival to discharge was 25%, with serum lactate $$\:\ge\:$$ 3 mmol/L at CRRT initiation being an independent predictor of mortality (adjusted OR 6.1, 95% CI: 1.1–34.9; P = 0.04). Major challenges faced in our program included the SARS-CoV-2 pandemic, non-availability of technical support, and out-of-pocket expenses. These were circumvented by involvement of fellows and nurses, training them with internal and external experts, and mobilizing resources from governmental and non-governmental organizations. Conclusion Initiating a CRRT program in LMICs is feasible despite challenges. Creating a team with members willing to shoulder additional responsibility and training them gave impetus to our program. Tapping governmental and non-governmental support helped us circumvent financial challenges. However, in a resource limited setting, sustainability requires in-house technical and financial support. Survival to discharge was 25%, with hyperlactatemia at CRRT initiation predicting mortality.